Preventing leptin resistance by blocking angiotensin II AT1 receptors in diet‐induced obese rats. (24th November 2014) - Müller‐Fielitz, Helge; Lau, Margot; Geißler, Cathleen; Werner, Lars; Winkler, Martina; Raasch, Walter
<x xml:space="preserve">Abstract</x> Background and Purpose AT1 receptor blockers (ARBs) represent an approach for treating metabolic syndrome due to their potency in reducing hypertension, body weight and onset of type 2 diabetes. The mechanism underlying ARB‐induced weight loss is still unclear. Experimental Approach Leptin resistance tests (LRTs) in diet‐induced obese or lean rats were conducted to determine whether telmisartan (8 mg·kg−1·day−1, 14 days) enhances leptin sensitivity. Phosphorylation of signal transducer and activator of transcription 3 (pSTAT3) staining was performed in hypothalami to determine leptin transport across the blood–brain barrier. Key Results Telmisartin reduced weight gain, food intake and plasma leptin but blood pressure remained unchanged. The 24 h profiles of plasma leptin after saline injections were similar in controls and telmisartan‐treated rats, but after leptin injections were higher in controls and slightly lower in telmisartan‐treated animals. After telmisartan, energy intake during LRT was lower in leptin‐ than in saline‐pretreated rats, but remained unchanged in controls, irrespectively of whether rats received saline or leptin. Leptin minimized the gain in body weight during LRT in telmisartan‐treated rats as compared with saline‐treated animals. pSTAT3 staining was reduced in cafeteria diet‐fed rats as compared with chow‐fed rats but this was normalized by telmisartan. Telmisartin reduced hypothalamic mRNA levels of the orexigenic peptides melanin‐concentrating hormone and prepro‐orexin. Conclusions and Implications Rats fed a cafeteria diet develop leptin resistance after 2 weeks. Leptin sensitivity was preserved by telmisartan treatment even in rats fed a cafeteria diet. This pleiotropic effect is not related to the hypotensive action of telmisartan.